Analisis Keputusan Pembelian Perumahan Pada PT Ardan Greenland Propertindo Purworejo - Agus Fitri Yanto; Dwi Irawati (Politeknik Sawunggalih Aji, 2022)
Increasingly increasing population makes the need for housing to increase. Seeing the increasing need for housing makes business in the housing sector wide open and growing. One company engaged in housing or property is PT Ardan Greenland Propertindo Purworejo. This study aims to analyze location, service and product quality factors towards housing purchase decisions at PT Ardan Greenland Propertindo Purworejo. This study uses a method that is